Makna Warna Oranye pada Logo E-Commerce Shopee dari Perspektif Semiotika Komunikasi Visual Ferdinand de Saussure - M. Denu Poyo; M. Haikal Junior; Hanindyalaila Pienrasmi (JUSTICE Journal Of Social and Political Science, 2026)
The rapid development of digital technology has positioned visual communication as a crucial instrument in building brand identity, particularly within the highly competitive e-commerce industry. As one of the largest ecommerce platforms in Indonesia, Shopee utilizes orange as the dominant element of its visual identity, serving as a medium for conveying messages and shaping brand image. This study aims to analyze the meaning of the orange color in the Shopee logo from the perspective of Ferdinand de Saussure’s visual communication semiotics. The theoretical framework employed includes visual communication theory, Ferdinand de Saussure’s semiotic theory focusing on the relationship between the signifier and the signified, as well as visual color theory and color psychology. This research adopts an interpretive paradigm with a qualitative descriptive approach and semiotic analysis as its primary method. Data were collected through visual document observation of the official Shopee logo, in-depth interviews with informants consisting of graphic design practitioners, branding practitioners, visual communication academics, and active Shopee users, and were supported by relevant literature studies. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, with validity ensured through source triangulation, technique triangulation, and member checking. The findings indicate that the orange color in the Shopee logo functions as a signifier representing energy, enthusiasm, warmth, creativity, optimism, and closeness to users. These meanings contribute to establishing a strong visual identity, enhancing brand recall, and reinforcing Shopee’s image as a modern, dynamic, accessible, and consumer-oriented e-commerce platform.